Trans-Spinal Direct Current Stimulation Targets Ca2+ Channels to Induce Persistent Motor Unit Responses - Song, Weiguo; Martin, John H. (Frontiers in Neuroscience, 2022)
Trans-spinal direct current stimulation (tsDCS) is a neuromodulatory approach to augment spinal cord activity to improve function after neurological disease and injury. Little is known about the mechanisms underlying tsDCS actions on the motor system. The purpose of this study is to determine the role for a persistent inward current (PIC)-like response in motoneurons in mediating tsDCS actions. We recorded single motor units from the extensor carpi radialis muscle in healthy sedated rats and measured unit activity changes produced by cathodal and anodal tsDCS (c-tsDCS; a-tsDCS) of the cervical enlargement. Both c-tsDCS and a-tsDCS immediately increased spontaneous motor unit firing during stimulation. After c-tsDCS was stopped, spontaneous firing persisted for a substantial period (165s ± 5s), yet after a-tsDCS activity shortly returned to baseline (27s ± 7s). Administration of the L-type calcium channel blocker Nimodipine reduced spontaneous motor unit firing during c-tsDCS and blocked the persistent response. By contrast, Nimodipine did not change unit firing during a-tsDCS but the short persistent response was blocked. Computer simulation using a two-compartment neuronal model replicated the main experimental observations: larger and more persistent responses during and after c-tsDCS than a-tsDCS. Using reduced Ca2+ conductance to model Nimodipine action, a reduced response during c-tsDCS and elimination of the persistent response was observed. Our experimental findings, supported by computer simulation, show that c-tsDCS can target Ca2+ conductances to augment motoneuron activity. As tsDCS is well-tolerated in humans, this knowledge informs therapeutic treatment strategies to achieve rehabilitation goals after injury; in particular, to increase muscle force.